Long-term trends in treatment and outcomes of patients with diabetes and acute coronary syndromes: insights from the nationwide AMIS plus registry. (14th October 2021) - Stahli, B; Witassek, F; Roffi, M; Eberli, F; Rickli, H; Erne, P; Maggiorini, M; Pedrazzini, G; Radovanovic, D
Abstract: Background: Although impressive advances in the treatment of patients with acute coronary syndromes (ACS) have been achieved over the last decades, morbidity and mortality of patients with diabetes and ACS remain substantial. This study aimed at investigating long-term trends in treatment and outcomes of patients with diabetes and ACS, using data from a large, prospective, nation-wide database. Methods: Patients with ST segment elevation myocardial infarction (STEMI) or non-ST segment elevation myocardial infarction (NSTEMI) enrolled in the prospective AMIS Plus registry between 01/2003 and 12/2018 and available data on diabetes diagnosis were included in the analysis. Major adverse cardiovascular events (MACE), a composite of all-cause death, non-fatal myocardial infarction, and cerebrovascular events were assessed for each 3-year period. Results: Out of 49'413 ACS patients, 10'200 (20.6%) had diabetes (29.4% women). In diabetic patients, the percentage of women decreased from 32.3% in 2002–2004 to 25.9% in 2017–2019 (p<0.001). Diabetic patients were older (p<0.001), more frequently women (p<0.001), and had a higher body mass index (p<0.001). They less often underwent percutaneous coronary intervention (p<0.001) and were more frequently treated by coronary artery bypass grafting (p<0.001). Over the 18-year period, the percentage of diabetic patients undergoing PCI or CABG increased (p<0.001). While treatment with glycoprotein IIb/IIIa inhibitors, low-molecular weight heparin, and beta blockers decreased over time, administration of aspirin, P2Y12 inhibitors, lipid-lowering drugs, and unfractionated heparin increased. Rates of MACE were 9.5% and 5.2% in diabetic and non-diabetic patients (p<0.001). Rates of mortality (7.7% versus 4.1%, p<0.001), recurrent myocardial infarction (1.5% versus 0.9%, p<0.001), and cerebrovascular events (1.2% versus 0.6%, p<0.001) were higher in diabetic as compared with non-diabetic patients, with highest rates of MACE, mortality, and myocardial infarction observed in diabetic women. Rates of MACE decreased from 11.8% in 2002–2004 to 7.5% in 2017–2019 in diabetic patients (p for trend <0.001). While rates of mortality (9.4% to 5.9%, p for trend =0.001) and rates of recurrent myocardial infarction (3.4% to 0.9%, p for trend <0.001) decreased over time, rates of cerebrovascular events remained stable (p for trend =0.34). Trends were the same in diabetic women and men. Conclusions: Rates of MACE significantly decreased over the 18-year period in both diabetic women and men, with highest rates observed in diabetic women. Despite the observed improvements, rates of MACE remained 50% higher in diabetic as compared with non-diabetic patients. These findings emphasize that advanced strategies particularly targeting the vulnerable high-risk diabetic patient population are warranted to further improve quality of care in ACS. Funding Acknowledgement: Type of funding sources: None.